Questions Students Have: A Solution for Improving the Islamic Education Learning Outcomes of Primary School Learners - Wahyuni, Yulia Septi; Istiqomah, Dina; Deprizon, Deprizon (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2024)
This research is motivated by the low learning outcomes of students in Islamic Religious Education subjects, which are indicated by the scores of students who are below the minimum completion criteria. This phenomenon can be seen from various obstacles in the learning process, which indicates less than optimal understanding of students. The research aims to analyze the Questions Students Have learning strategy in improving students' learning outcomes in Islamic schools in Indonesia. The research was conducted in two cycles, each consisting of two meetings. To ensure a smooth process, the research was designed through four main stages, namely planning, implementation, observation, and reflection. The results showed that it has been able to improve students' learning outcomes. Before the action was taken, the percentage of students who reached the minimum completion criteria was only 43.8%, which was categorized as less. After the implementation of the strategy in cycle I, the figure increased to 68.8%, and in cycle II it reached 87.5%, which is classified as a good category. This finding proves that the Questions Students Have learning strategy is effective in improving learning outcomes in Islamic religious education subjects.